ln(x)+ln(x-3e)=ln(4)+2

Simple and best practice solution for ln(x)+ln(x-3e)=ln(4)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x)+ln(x-3e)=ln(4)+2 equation:


Simplifying
ln(x) + ln(x + -3e) = ln(4) + 2

Multiply ln * x
lnx + ln(x + -3e) = ln(4) + 2

Reorder the terms:
lnx + ln(-3e + x) = ln(4) + 2
lnx + (-3e * ln + x * ln) = ln(4) + 2
lnx + (-3eln + lnx) = ln(4) + 2

Reorder the terms:
-3eln + lnx + lnx = ln(4) + 2

Combine like terms: lnx + lnx = 2lnx
-3eln + 2lnx = ln(4) + 2

Reorder the terms for easier multiplication:
-3eln + 2lnx = 4ln + 2

Reorder the terms:
-3eln + 2lnx = 2 + 4ln

Solving
-3eln + 2lnx = 2 + 4ln

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '-2lnx' to each side of the equation.
-3eln + 2lnx + -2lnx = 2 + 4ln + -2lnx

Combine like terms: 2lnx + -2lnx = 0
-3eln + 0 = 2 + 4ln + -2lnx
-3eln = 2 + 4ln + -2lnx

Divide each side by '-3ln'.
e = -0.6666666667l-1n-1 + -1.333333333 + 0.6666666667x

Simplifying
e = -0.6666666667l-1n-1 + -1.333333333 + 0.6666666667x

Reorder the terms:
e = -1.333333333 + -0.6666666667l-1n-1 + 0.6666666667x

See similar equations:

| 59=4k-7+3+5k | | 2x^2+4x+60=0 | | 7-4(-x+3)=2x | | -10g^2+13g=4 | | 14=9+3y-2y | | -6g^2+9g+8=0 | | 4(v-4)-6v=-8 | | 3(10)+5(x)=75 | | 5(3x+1)-2(5x+35)=0 | | 3(-4)-2(-2*3)+9= | | -4(v-2)=-4(v-8)+8v | | -(x-2)=2-x | | 6+5m-4=9m+20-6m | | 3x+2x=54 | | -0.9x+2.65=-0.5x+5.45 | | 15+5n=6n | | 5x-20=15y+60 | | 2x-5=6x+4 | | 2y^2+17y+35= | | -4x+3=7x-8 | | 3x+8.13=2x | | 9x^2+60x=-100 | | 2x^2-4x+100=100 | | 15-5(1-1)=120-5 | | 4*2+10y=40 | | x^4+2x^3-x^2-x+1=0 | | 2(x-3)+x=3(x-5)+9 | | 6.5=10x+7.2 | | 2x+2(9x-9)-2x^2=13-28-3x^2+10 | | ax-3x+5=a+b | | X*(X-5)=176 | | 9(x-8)+4=9x+6 |

Equations solver categories